A realist review of health passports for Autistic adults - Ellis, Rebecca; Williams, Kathryn; Brown, Amy; Healer, Eleanor; Grant, Aimee (PLOS ONE, 2023)
Background Autism is a normal part of cognitive diversity, resulting in communication and sensory processing differences, which can become disabling in a neurotypical world. Autistic people have an increased likelihood of physical and mental co-occurring conditions and die earlier than neurotypical peers. Inaccessible healthcare may contribute to this. Autism Health Passports (AHPs) are paper-based or digital tools which can be used to describe healthcare accessibility needs; they are recommended in UK clinical guidance. However, questions remained as to the theoretical underpinnings and effectiveness of AHPs. Methods We undertook a systematic literature search identifying studies focused on AHPs for adults (aged over 16 years) from five databases. Included literature was subjected to realist evaluation. Data were extracted using a standardised form, developed by the research team, which considered research design, study quality for realist review and the Context, Mechanisms and Outcomes (CMOs) associated with each AHP tool. Findings 162 unique records were identified, and 13 items were included in the review. Only one item was considered high quality. Contextual factors focused on the inaccessibility of healthcare to Autistic patients and staff lack of confidence and training in supporting Autistic needs. Interventions were heterogeneous, with most sources reporting few details as to how they had been developed. The most frequently included contents were communication preferences. Mechanisms were often not stated or were inferred by the reviewers and lacked specificity. Outcomes were included in four studies and were primarily focused on AHP uptake, rather than Outcomes which measured impact. Conclusion There is insufficient evidence to conclude that AHPs reduce the health inequalities experienced by Autistic people. Using an AHP tool alone in a healthcare Context that does not meet Autistic needs, without the inclusion of the local Autistic community developing the tool, and a wider intervention to reduce known barriers to health inequality, may mean that AHPs do not trigger any Mechanisms, and thus cannot affect Outcomes.